Pustakawan sebagai Konselor di Era Distrupsi - Azwar, Azwar (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
Information technology changes the order of information retrieval. Librarians in the era of disruption are no longer limited to managing collections and technical services, but have developed into facilitators, companions for personal development of users. Librarians as counselors must have interpersonal and communication skills, as well as a basic understanding of counseling to help users solve problems of fulfilling information, academic, social, and emotional needs. This study aims to explore the role of librarians as counselors. Literature studies are used for this research method. The results of this study indicate that librarians as counselors help users in fulfilling information, building emotional bonds. So that users are able to become independent people in retrieving information in the future.